Pengaruh Usia, Pendidikan Suami, Dan Pekerjaan Terhadap Kemandirian Pendidikan Anak Dalam Keluarga - Fitria, Baiq Arda Nurul; Muh. Huzaini; Vici Handalusia Husni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of age, husband's education, and husband's occupation on children's educational decision-making within the family. This study used a logistic regression model. The results showed that only the husband's education had a significant influence on children's independence in education. Meanwhile, the variables of age and husband's occupation did not show a significant influence. The regression coefficient indicates that the higher the husband's education level, the greater the likelihood of children receiving a better education. However, the regression model used in this study was only able to explain approximately 6.05% of the variation in children's educational independence. This study concluded that the husband's education was the only factor that significantly influenced independence, while the husband's age and type of occupation did not. For a better model, it is necessary to add other variables that may be more relevant. Keywords: Age, Husband’s Education, Husband’s Occupation, Independence, Children’s Education, Logistic Regression.